2015
DOI: 10.1177/1035304615571225
|View full text |Cite
|
Sign up to set email alerts
|

Trade openness and unemployment: Empirical evidence for Nigeria

Abstract: In the wake of the global financial crisis, unemployment rates and openness to trade have been the subject of considerable research, especially in developing countries. This study analyses the impacts of trade policy on unemployment rates in Nigeria. Using time series data from 1970 to 2010, it adopts the vector error correction methodology. In order to explore the impact of a range of variables on the relationship between trade openness and national unemployment rates, these variables, in a system of equation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
1
2

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 44 publications
3
23
1
2
Order By: Relevance
“…This result may be attributed to the labor institutional market condition in the country because it has been argued that where there is pronounced restrictive labor market regulation and more prevalent of informal labor market, trade openness may worsen unemployment rate (Menezes-Filho and Muendler, 2011). Our results are also akin to the finding of Nwaka et al, (2015) who found that trade liberalization proxied by trade openness worsens unemployment in Nigeria.…”
Section: Short-run and Long-run Ardl Model Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…This result may be attributed to the labor institutional market condition in the country because it has been argued that where there is pronounced restrictive labor market regulation and more prevalent of informal labor market, trade openness may worsen unemployment rate (Menezes-Filho and Muendler, 2011). Our results are also akin to the finding of Nwaka et al, (2015) who found that trade liberalization proxied by trade openness worsens unemployment in Nigeria.…”
Section: Short-run and Long-run Ardl Model Resultssupporting
confidence: 71%
“…On the impact of international trade on unemployment rate, studies are inexhaustible but characterized with mixed findings. While some studies such as Felbrermayr et al (2009); Dutt, Mitra and Ranjan, (2009), Kim (2011), Loganathan et al, (2011), Hassan, et al (2012 as well as Anyanwu, (2014) agreed that trade openness and unemployment were inversely related, that is, trade openness reduced unemployment, there were ample of other studies such as Davis (1998), Egger and Kreickemeier (2009), Helpman and Itskhoki (2010) and Nwaka, et al (2015) suggested that trade openness worsened unemployment. Deviation from the two contracting sides above are the studies such as Sener 2001and Moore and Ranjan (2005) who concluded that trade openness had no direct effect on unemployment.…”
Section: Empirical Literature Reviewmentioning
confidence: 99%
“…Although the unemployment crisis in Nigeria has drawn the attention of many researchers over the years, however, most of the available studies have focused more on the impacts of unemployment on the growth of the economy with the exception of a few that have viewed unemployment challenges from the trade perspective. Nwaka, Uma, and Tuna (), in their study, adopted the vector error correction technique (VECM) in analyzing time series data from Nigeria between 1970 and 2010, and their results showed that trade openness is associated with rising unemployment in Nigeria. Furthermore, some studies have also focused on investigating the determinants of unemployment within the context of the Nigerian economy for instance; Orji, Orji‐Anthony, and Okafor () investigated the unemployment inflation relationship in Nigeria and obtained a significant positive relationship among these two variables.…”
Section: Literature Of Related Reviewmentioning
confidence: 99%
“…According to the alternative panel data estimations presented in Table 4, the variables reflecting the situation of economic activity may have a positive impact on unemployment, except for gross fixed capital formation, in line with Bande and Riveiro (2012), who found that consumption shocks had a lowering impact on unemployment, while we show that investment shocks led to an increase in the unemployment rates in these countries. Thereby, it can be deduced that increases in consumption and investments and rising inflation may have consequences for the labor market by affecting the labor demand and supply, similar to Karanassou et al (2008), Ciccarone et al (2014), Gozgor (2014) and Nwaka et al (2015). Moreover, we can infer that growth in the aggregate demand may lead to a push in the demand for labor in the G10 countries, which in turn may increase the real wage and promote an increase in the labor supply.…”
Section: Findings and Discussionmentioning
confidence: 92%